(untitled) (One Health & Risk Management, 2023)
Introduction. Nowadays the worldwide women population including Georgian women is still at high risk of ovarian cancer. As it is well known, the main cause of ovarian cancer is HPV. For effective HPV prevention globally, assessment of knowledge about Human Papillomavirus in women by healthcare providers is significantly important for positive results for disease prevention. But most importantly to reduce the occurrence of ovarian cancer worldwide, healthcare workers must be fully informed about HPV. Aim. Evaluate primary healthcare providers ‘awareness about HPV infection and prevention. Material and methods. Between June and July 2022, a cross-sectional survey was delivered to primary healthcare personnel in several ambulatories in Tbilisi and Rustavi. To assess the awareness of HPV among primary healthcare workers, adapted versions of HPV awareness evaluation questionnaires were used based on the same studies in different countries. Statistical Analysis was performed in IBM SPSS Statistics 23. We used Fisher’s Exact Test to find any associations between sex and awareness about HPV, working position and awareness of HPV, age and awareness of HPV, workplace location and awareness of HPV. P value <0.05 was considered statistically significant. Results. Of more than 200 doctors only 71 are willing to participate in the survey and fully fill in the electronic survey form. Although overall understanding of essential HPV facts was appropriate, the participants’ average general HPV knowledge score was 12 out of a possible total of fourteen. Furthermore, the prevalence of right responses was 85.8 percent of the total number of doctors. 43.7% of respondents correctly recognized that HPV does not require treatment. 11.7% of respondents believed that HPV is rare and what is more 29,6 percent do not have information about different types of HPV. Overall, primary healthcare practitioners performed well on the HPV triage and cure route exam, with a median score of 6 out of 9. However, there was considerable confusion about the objective of the HPV test. 29.6% were unaware of the aim of the HPV test. Although the overall knowledge score for HPV screening and vaccines was normal, detailed information proved to be lacking: 59%were unaware of the suggested age for receiving a pap smear. The duration of time between HPV tests was also significantly misunderstood, with only 39.4% knowing the right time frame for HPV testing. In any of the three examined knowledge areas, primary healthcare workers’ age and gender did not correlate with HPV knowledge. Even though most of the study population were younger there is still no statistically significant difference among younger and older generations of primary healthcare workers. In any of the three examined knowledge areas, primary healthcare workers’ specialty and clinic location where they work did not correlate with HPV knowledge. Conclusions. It is our first study in Georgia to investigate health professionals’ knowledge and understanding of HPV, vaccination, and HPV screening. Although overall knowledge was appropriate, major gaps in knowledge existed, notably on the importance of HPV vaccine and screening knowledge. It is important to raise awareness about vaccination to promote reduction of ovarian cancer risk.